The effect of cannabis-derived terpenes on alveolar macrophage function - Patrick M. Greiss; Patrick M. Greiss; Patrick M. Greiss; Jacquelyn D. Rich; Jacquelyn D. Rich; Jacquelyn D. Rich; Geoffrey A. McKay; Dao Nguyen; Dao Nguyen; Dao Nguyen; Dao Nguyen; Mark G. Lefsrud; et al. (Frontiers in Toxicology)
Cannabis sativa (marijuana) is used by millions of people around the world. C. sativa produces hundreds of secondary metabolites including cannabinoids, flavones and terpenes. Terpenes are a broad class of organic compounds that give cannabis and other plants its aroma. Previous studies have demonstrated that terpenes may exert anti-inflammatory properties on immune cells. However, it is not known whether terpenes derived from cannabis alone or in combination with the cannabinoid ∆9-THC impacts the function of alveolar macrophages, a specialized pulmonary innate immune cell that is important in host defense against pathogens. Therefore, we investigated the immunomodulatory properties of two commercially-available cannabis terpene mixtures on the function of MH-S cells, a murine alveolar macrophage cell line. MH-S cells were exposed to terpene mixtures at sublethal doses and to the bacterial product lipopolysaccharide (LPS). We measured inflammatory cytokine levels using qRT-PCR and multiplex ELISA, as well as phagocytosis of opsonized IgG-coated beads or mCherry-expressing Escherichia coli via flow cytometry. Neither terpene mixture affected inflammatory cytokine production by MH-S cells in response to LPS. Terpenes increased MH-S cell uptake of opsonized beads but had no effect on phagocytosis of E. coli. Addition of ∆9-THC to terpenes did not potentiate cytotoxicity nor phagocytosis. These results suggest that terpenes from cannabis have minimal impact on the function of alveolar macrophages.